Cesarean scar pregnancy and early placenta accreta share common histology. (April 2014) - Timor‐Tritsch, I. E.; Monteagudo, A.; Cali, G.; Palacios‐Jaraquemada, J. M.; Maymon, R.; Arslan, A. A.; Patil, N.; Popiolek, D.; Mittal, K. R.
ABSTRACT Objective To determine, by evaluation of histological slides, images and descriptions of early (second‐trimester) placenta accreta (EPA) and placental implantation in cases of Cesarean scar pregnancy (CSP), whether these are pathologically indistinguishable and whether they both represent different stages in the disease continuum leading to morbidly adherent placenta in the third trimester. Methods The database of a previously published review of CSP and EPA was used to identify articles with histopathological descriptions and electronic images for pathological review. When possible, microscopic slides and/or paraffin blocks were obtained from the original researchers. We also included from our own institutions cases of CSP and EPA for which pathology specimens were available. Two pathologists examined all the material independently and, blinded to each other's findings, provided a pathological diagnosis based on microscopic appearance. Interobserver agreement in diagnosis was determined. Results Forty articles were identified, which included 31 cases of CSP and 13 cases of EPA containing histopathological descriptions and/or images of the pathology. We additionally included six cases of CSP and eight cases of EPA from our own institutions, giving a total of 58 cases available for histological evaluation (37 CSP and 21 EPA) containing clear definitions of morbidly adherent placenta. In the 29 cases for which images/slides were available for histopathological evaluation, both pathologists attested to the various degrees of myometrial and/or scar tissue invasion by placental villi with scant or no intervening decidua, consistent with the classic definition of morbidly adherent placenta. Based on the reviewed material, cases with a diagnosis of EPA and those with a diagnosis of CSP showed identical histopathological features. Interobserver correlation was high (kappa = 0.93). Conclusions EPA and placental implantation in CSP are histopathologically indistinguishable and may represent different stages in the disease continuum leading to morbidly adherent placenta in the third trimester. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.